Evaluation of Some Haematological Inflammatory Parameters in Type 2 Diabetes Mellitus and its Relationship with Glycemic Control and Disease Complications - Ghsin Al-ban Adnan Ouda; Suaad Mohammed H. Rasheed (مجلة الكوفة الطبية)
Background: Haematological inflammatory indices is a cheap, available and practical laboratory markers reflect the inflammatory process. purpose: to investigate the association between some haematolgical indices and diabetes control and complications in Iraqi diabetic patients.  Methods: In a case-control study, 78 patients with a documented history of type 2 diabetes mellitus (T2DM) were recruited and matched in regard to age and sex with 57 non diabetic volunteers. RBS, HbA1c and CBP were analyzed. Results: diabetic patients had higher but non-significant increments in platelets, absolute neutrophil count, absolute lymphocyte count, Neutrophil Lymphocyte ratio (NLR), and Platelets Lymphocyte ratio (PLR) in comparison to controls. The mean platelets count was significant higher in patients with poor glycemic control in compared to patients with good glycemic control, (269.3 ± 16.53 vs. 206.33 ± 20.26) respectively, (P <0.001) while the NLR and PLR not associated with glycemic control. The studied hematological indices were associated but with no statistical significant with diabetic complications (P< 0.05). Conclusion: hematological parameters not associated with diabetes control or complications in Iraqi patients.